ASUPAN BAHASA UNTUK PENDIDIKAN KARAKTER ANAK USIA DINI - Rahmat (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
Every parent wants their children to be better than themselves, both in terms of emotional intelligence and spiritual intelligence. This intelligence can be reflected in the attitudes and behavior of children. Attitudes and behavior in the linguistic field are called speech acts. The child's speech acts that every parent wants include politeness, responsibility, honesty, self-confidence, independence, discipline, humility, mutual help, love for others, creativity, caring for others, and religious. All of these are values ??that exist in character education. Children need to be instilled in character education so that future generations will be even better. Character planting can be done by providing language intakes to early childhood. Based on Skinner's behaviorism theory, language acquisition in early childhood can be done by stimulus or language intakes. Provision of intake can be adjusted to the desired character values ??of parents. Then, it is hoped that the children will respond with actions and speech. All actions and speech of the child will be adjusted to the achievement of the desired character values. The results found that language intake was in the form of: (a) invitation sentences such as, “Dek, let's pray!”; (2) interjections in the form of thayibah sentences, such as alhamdulillah; (3) prohibition sentences, such as